Interaction between Dietary Vitamin D3 and Vitamin K3 in Gilthead Seabream Larvae (Sparus aurata) in Relation to Growth and Expression of Bone Development-Related Genes - U. Sivagurunathan; David Dominguez; Yiyen Tseng; María Jesús Zamorano; Antony Jesu Prabhu Philip; Marisol Izquierdo (Aquaculture Nutrition)
Vitamins D and K are essential fat-soluble nutrients that intervene in bone development processes among other biological functions. The present study is aimed at investigating the potential combined effect of dietary supplementation with vitamin D3 (cholecalciferol) and vitamin K3 (menadione) in gilthead seabream (Sparus aurata) larvae. For that purpose, seabream diets were supplemented with different combinations of vitamin D3/vitamin K3 (mg/kg diet) as follows: 0.00/0, 0.06/70, 0.06/170, 0.13/70, 0.13/170, 0.40/70, and 0.40/170. Feeding gilthead seabream larvae (22 days post hatch) for 21 days with the diets supplemented with 0.06-0.13 mg/kg vitamin D3 and 70 mg/kg vitamin K3 (diets 0.06/70 and 0.13/70) led to the highest larval growth and survival and the highest expression of important biomarkers of both bone development and health, such as bmp2, osx, and mgp, and calcium homeostasis, such as pthrp and casr. However, the increased supplementation with both vitamins at 0.40 mg/kg vitamin D3 and 170 mg/kg vitamin K3 (diet 0.40/170) reduced larval growth and survival, downregulated bmp2 and pthrp expressions, and upregulated osx and mgp, causing an unbalance in the relative expression of these genes. The results of the present study have shown the interaction between vitamin D3 supplementation and vitamin K3 supplementation in larval performance and gene expression related to bone development and calcium homeostasis, denoting the significance of a correct balance between both vitamins in larval diets.